Micro phase separated epoxy/poly(ε-caprolactone)-block-poly(dimethyl siloxane)-block-poly(ε-caprolactone)/4, 4′-diaminodiphenylsulfone systems: Morphology, viscoelasticity, thermo-mechanical properties and surface hydrophobicity. (October 2016) - Parameswaranpillai, Jyotishkumar; Sidhardhan, Sisanth Krishnan; Jose, Seno; Salim, Nisa V.; Siengchin, Suchart; Pionteck, Jürgen; Magueresse, Anthony; Grohens, Yves; Hameed, Nishar
Abstract: Epoxy resin/4, 4′-diaminodiphenylsulfone (DDS) system was modified by the incorporation of poly(ε-caprolactone)-block-poly(dimethyl siloxane)-block-poly(ε-caprolactone) (PCL–PDMS–PCL) triblock copolymer (TBCP). Morphology, viscoelasticity, thermo-mechanical and surface properties of these blends were investigated. All the blends were opaque after curing. PCL blocks of the TBCP were miscible with epoxy resin while the PDMS fraction was immiscible. However in the cured state, both PCL and PDMS blocks were phase separated from epoxy/DDS matrix. The blends exhibited matrix-droplet morphology in which TBCP phase dispersed as spherical domains in epoxy matrix. Addition of TBCP had profound impact on the cure reaction kinetics. Storage modulus and glass transition temperature ( T g ) decreased while impact strength significantly increased. Incorporation of 15 phr of TBCP resulted in 80% improvement in impact strength. Further, thermal stability was unaffected while surface hydrophobicity of the blends increased.